Ageing has no effect on the regulation of the ubiquitin proteasome-related genes and proteins following resistance exercise - Stefanetti, Renae J.; Zacharewicz, Evelyn; Della Gatta, Paul; Garnham, Andrew; Russell, Aaron P.; Lamon, Severine (Frontiers in Physiology, 2014)
Skeletal muscle atrophy is a critical component of the ageing process. Age-related muscle wasting is due to disrupted muscle protein turnover, a process mediated in part by the ubiquitin proteasome pathway (UPP). Additionally, older subjects have been observed to have an attenuated anabolic response, at both the molecular and physiological levels, following a single-bout of resistance exercise (RE). We investigated the expression levels of the UPP-related genes and proteins involved in muscle protein degradation in 10 older (60-75 years) versus 10 younger (18-30 years) healthy male subjects at basal as well as 2 hours after a single-bout of RE. MURF1, atrogin-1 and FBXO40, their substrate targets PKM2, myogenin, MYOD, MHC and EIF3F as well as MURF1 and atrogin-1 transcriptional regulators FOXO1 and FOXO3 gene and/or protein expression levels were measured via real time PCR and western blotting, respectively. At basal, no age-related difference was observed in the gene/protein levels of atrogin-1, MURF1, myogenin, MYOD and FOXO1/3. However, a decrease in FBXO40 mRNA and protein levels was observed in older subjects, while PKM2 protein was increased in older subjects. In response to RE, MURF1, atrogin-1 and FBXO40 mRNA were upregulated in both the younger and older subjects, with changes observed in protein levels. In conclusion, UPP-related gene/protein expression is comparably regulated in healthy young and old male subjects at basal and following RE. These findings suggest that UPP signalling plays a limited role in the process of age-related muscle wasting. Future studies are required to investigate additional proteolytic mechanisms in conjunction with skeletal muscle protein breakdown measurements following RE in older versus younger subjects.